2009
DOI: 10.1016/j.ajog.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Does mental imagery prior to cystoscopy make a difference? A randomized controlled trial

Abstract: OBJECTIVE We sought to determine whether mental imagery improves surgical performance of residents novice to cystoscopy. STUDY DESIGN We performed a multicenter randomized controlled trial. Residents who had performed ≤ 3 cystoscopies were randomized to preoperative mental imagery sessions or reading a book chapter describing cystoscopy. The primary outcome was comparison of groups’ surgical performance scores. Secondary outcomes were measurements of operative times and resident ratings of helpfulness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 16 publications
0
63
2
2
Order By: Relevance
“…In a randomised controlled trial by Komesu et al, 22 junior residents improved in the performance of a cystoscopy after MI when compared with a control group. Scores were 15.9% higher than controls (P = 0.03).…”
Section: No MI Groupmentioning
confidence: 97%
“…In a randomised controlled trial by Komesu et al, 22 junior residents improved in the performance of a cystoscopy after MI when compared with a control group. Scores were 15.9% higher than controls (P = 0.03).…”
Section: No MI Groupmentioning
confidence: 97%
“…22 Further, Arora et al (2010b) performed a study with 10 experienced surgeons (>100 LCs) and 10 novice surgeons (< 10 LCs) to develop and validate imagery as a training technique for laparoscopic surgery. 23 They found that after undergoing imagery training for the LC procedure, novice surgeons significantly improved their knowledge and confidence to perform a LC, and their ability to imagine the LC procedure.…”
Section: Mental Imagerymentioning
confidence: 99%
“…Imagery has been shown to be a cost-effective training supplement to physical practice that cuts down on resource consumption, [12][13]17,23,29,31 and enhances surgeons' performance through improved acquisition and performance of surgical skills, [13][14][15][16][18][19]22,24,[29][30] knowledge, 11,23,26 confidence, 23,[26][27] and team-based skills. 25 …”
Section: Mental Imagerymentioning
confidence: 99%
“…[4][5][6][7][8][15][16][17] The current evidence in surgical disciplines suggests that MP is a safe and cost-effective method for training novice surgeons in technical procedures. 8,16,17 A randomized controlled trial by Arora et al found MP to be beneficial for enhancing the imagery and performance of novice surgeons during a simulated laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%